1997
DOI: 10.1590/s0104-66321997000400014
|View full text |Cite
|
Sign up to set email alerts
|

INFLUENCE OF PHOSPHATE CONCENTRATIONS ON GLUCOAMYLASE PRODUCTION BY Aspergillus awamori IN SUBMERGED CULTURE

Abstract: The aim of this work was to study the influence of phosphate concentrations on glucoamylase production by the fungus Aspergillus awamori. In culture media containing cassava flour, different levels of phosphates were tested and the fungal responses to increasing levels (whether or not coupled to pH adjustment throughout the run) were assessed in terms of the resulting glucoamylase production. Phosphate increments, associated with pH readjustments throughout the run, yielded around 1,200 U/L of quite stable glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
1
4
0
1
Order By: Relevance
“…Similar results were obtained by [17]. Moreover, [42] reported that the synthesis of a-amylase is stimulated by adding phosphorus to the culture medium and the concentration recommended is 7.0-10.0 g/l.…”
Section: ) Production Of A-amylasesupporting
confidence: 87%
“…Similar results were obtained by [17]. Moreover, [42] reported that the synthesis of a-amylase is stimulated by adding phosphorus to the culture medium and the concentration recommended is 7.0-10.0 g/l.…”
Section: ) Production Of A-amylasesupporting
confidence: 87%
“…Their concentration in the medium and type of source (inorganic or organic) can stimulate or inhibit the laccase production. Effect of phosphate on glucoamylase production showed a positive correlation . It is known that high concentration of ATP leads to enzyme secretion in fungi .…”
Section: Resultsmentioning
confidence: 87%
“…Effect of phosphate on glucoamylase production showed a positive correlation. 29 It is known that high concentration of ATP leads to enzyme secretion in fungi. 30 Laccase production media that are already reported for prokaryotes coincidently contain rarely more than 10 mM of inorganic phosphate.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Zaldivar-Aguero et al, (40) reported that the synthesis of α-amylase is stimulated by adding 7.0 to 10.0 g/L phosphorus to the culture medium. In contrast, Jin et al, (30) did not obtain a significant improvement in gluco-amylase yields by adding phosphorus to the fermentation medium.…”
Section: Optimization Of α-Amylase Productionmentioning
confidence: 99%